20th European Meeting on Supercritical Fluids: Book of Abstracts - Knez, Željko; Pantić, Milica; Cör Andrejč, Darija (2024)
The 20th European Meeting on Supercritical Fluids (EMSF 2024) was hosted by the Faculty of Chemistry and Chemical Engineering of the University of Maribor from 26 May to 29 May 2024 in Maribor, Slovenia. The EMSF 2024 was a joint event of the International Society for the Advancement of Supercritical Fluids (ISASF) and the European Federation of Chemical Engineering (EFCE) Working Party on High Pressure Technology (WP HPT) Event No. 807. This symposium provided an excellent opportunity for engineers, chemists, physicists, food technologists, and biologists to meet and discuss new ideas, review ongoing challenges, present potential solutions, and identify future issues related to high pressure technologies and supercritical fluids. The aim of the meeting was to deepen connections between researchers, establish new contacts, and promote synergies and partnerships between researchers. The symposium presented the latest advances in high-pressure process technologies that can contribute to the further development of the field.
Keywords: supercritical fluids; fundamental data; novel materials; industrial applications; research and development